PENGARUH KEPUASAN KERJA TERHADAP KOMITMEN ORGANISASI PEGAWAI NON PNS DI DINAS PENDIDIKAN PROVINSI JAWA BARAT - Yosa Jessica Nabila (Jurnal Tata Kelola Pendidikan, 2021)
This research aims to know the influence of job satisfaction on organizational commitment of non-civil servant employees in The West Java Provincial Departement Of Education. The method used in this research was a descriptive method with a quantitative approach. The data collection technique used was questionnaire that distributed to 83 research respondents. The WMS (Weight Mean Score) calculation result shows that of both variable X and variable Y is at good category. The correlation coefficient between Job Satisfaction and Organizational Commitment obtained a score of 0.644, which was included in the "strong" category. Meanwhile, the result of significance test shows the value of tcalculation for 7,572 and ttable for 1,989 (tcalculation ttable), it means that there is a significant relationship between variable X and variable Y. The influence of the Job Satisfaction on Organizational Commitment obtained from from the results of the determination test is 41.4% and the rest is influenced by other factors. The result of coefficient of determinition test shows 40,393 + 0,644X, means that each addition on the X variable will increase the Y variable value of 0.644. Based on the result, it can be concluded that there is a positive and significant influence between the Job Satisfaction On Organizational Commitment Of Non-Civil Servant Employees In The West Java Provincial Departement Of Education.